2022
DOI: 10.1097/scs.0000000000008849
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Evaluating the Efficacy of Intrathecal Fluorescein for Localizing Cerebrospinal Fluid Rhinorrhea

Abstract: Objectives: A defect in the skull base can result in leakage of cerebrospinal fluid (CSF) out of the subarachnoid space into the sinonasal cavities, termed CSF rhinorrhea. Patients presenting with CSF rhinorrhea often require surgical repair, typically performed endoscopically. Successful surgical intervention is highly reliant on accurate identification of the leak site. Identification can be enhanced by the administration of intrathecal fluorescein (IF) via a lumbar drain before surgery. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Fluorescein changes to a green color upon contact with CSF, and having the patient perform a Valsalva maneuver may lead to confirmation and localization 11 . A systematic review of seven studies found this to have a diagnostic accuracy rate of >96%, 12 though another systematic review astutely pointed out that only three studies before 2021 were utilized as pre‐operative diagnostic tools (as opposed to intraoperative), and all located already confirmed leaks 13 . Nevertheless, patients may not be actively leaking during the time of examination, which may be due to concurrent inflammation or a ball‐valve effect with intracranial contents during periods of low intracranial pressure 4,6,7 …”
Section: Current Methods In Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescein changes to a green color upon contact with CSF, and having the patient perform a Valsalva maneuver may lead to confirmation and localization 11 . A systematic review of seven studies found this to have a diagnostic accuracy rate of >96%, 12 though another systematic review astutely pointed out that only three studies before 2021 were utilized as pre‐operative diagnostic tools (as opposed to intraoperative), and all located already confirmed leaks 13 . Nevertheless, patients may not be actively leaking during the time of examination, which may be due to concurrent inflammation or a ball‐valve effect with intracranial contents during periods of low intracranial pressure 4,6,7 …”
Section: Current Methods In Diagnosismentioning
confidence: 99%
“…If done for the purposes of diagnosis, providers may opt for intrathecal fluorescein injection, which dyes CSF green and can be further visualized in the nasal cavity with a blue light filter (Figure 3). 4 Two systematic reviews have been published on the topic in the last few years, with results suggesting a >78% success rate in localization, though this varies with fluorescein dose 39,40 . False negatives can be obtained in patients with lumbar stenosis, insufficient dosing, small defects that ball‐valve with intracranial content, low CSF volume, and adhesions in prior meningitis patients 11 .…”
Section: Current Methods In Diagnosismentioning
confidence: 99%
See 1 more Smart Citation